The ethnomedicine, phytochemistry, and pharmacological properties of the genus Bersama: current review and future perspectives - Nigussie, Gashaw; Ashenef, Sintayehu; Meresa, Asfaw (Frontiers in Pharmacology, 2024)
Bersama (Melianthaceae) has been used in traditional medicine for a wide range of ailments, including blood purifier, immune booster, psychotropic medication, and treatment for malaria, hepatitis, infertility, diabetes, impotency, meningitis, and stroke. This review gathers fragmented information from the literature on ethnomedicinal applications, phytochemistry, pharmacology, and toxicology of the Bersama genus. It also explores the therapeutic potential of the Bersama genus in ethnophytopharmacology, allowing for further investigation. All the available information published in the English language on Bersama genus was compiled from electronic databases such as Academic Journals, Ethnobotany, Google Scholar, PubMed, Science Direct, Web of Science, and library search using the following keywords: -Bersama genus,‖ -traditional use,‖ -phytochemistry,‖ -pharmacological effects,‖ and -toxicology‖. The ethnomedical applications of the Bersama genus have been recorded, and it has been used traditionally for more than 30 different types of ailments. Thus far, more than 50 compounds have been isolated from the genus. Cardiac glycosides and terpenoids are the main compounds isolated from the Bersama genus. Different plant parts of Bersama genus extracts demonstrated a wide range of pharmacological properties, including antioxidant, antimalarial, antidiabetic, antiviral, anti-inflammatory, and cytotoxic activity. Exemplary drug leads from the genus include mangiferin and quercetin-3-O-arabinopyranoside, both of which have antioxidant activities. Bersama genus has long been used to cure a wide range of ailments. Bersama genus extracts and phytochemicals have been found to have promising pharmacological activities. Further study on promising crude extracts and compounds is required to develop innovative therapeutic candidates.